Sugarcane straw returning is an approaching technique for the improvement of rhizosphere soil functionality, microbial community, and yield of different sugarcane cultivars - Wang, Mengrong; Qi, Xiaohang; Shi, Yujie; Zhao, Junyang; Ahmad, Shakeel; Akhtar, Kashif; Chen, Baoshan; Lian, Tengxiang; He, Bing; Wen, Ronghui (Frontiers in Microbiology, 2023)
Sugarcane straw returned to the field has rapidly increased due to the bane on straw burning in China. Straw returning of new sugarcane cultivars has been practiced in the fields. Still, its response has not been explored on soil functionality, microbial community and yield of different sugarcane cultivars. Therefore, a comparison was made between an old sugarcane cultivar, ROC22 and a new sugarcane cultivar, Zhongzhe9 (Z9). The experimental treatments were: without (R, Z), with straw of the same cultivar (RR, ZZ), and with straw of different cultivars (RZ, ZR). Straw returning improved the contents of soil total nitrogen (TN by 73.21%), nitrate nitrogen (NO3—N by 119.61%), soil organic carbon (SOC by 20.16%), and available potassium (AK by 90.65%) at the jointing stage and were not significant at the seedling stage. The contents of NO3—N was 31.94% and 29.58%, available phosphorus (AP 53.21% and 27.19%), and available potassium (AK 42.43% and 11.92%) in RR and ZZ were more than in RZ and ZR. Straw returning with the same cultivar (RR, ZZ) significantly increased the richness and diversity of the rhizosphere microbial community. The microbial diversity of straw returning from cultivar Z9 (treatment Z) was greater than that of cultivar ROC22 (Treatment R). In the rhizosphere, the relative abundance of beneficial microorganisms Gemmatimonadaceae, Trechispora, Streptomyces, Chaetomium, etc., increased after the straw returned. Sugarcane straw enhanced the activity of Pseudomonas and Aspergillus and thus increased the yield of sugarcane. , The richness and diversity of the rhizosphere microbial community of Z9 increased at maturity. In ROC22, bacterial diversity increased, and fungal diversity decreased. These findings collectively suggested that the impact of Z9 straw returning was more beneficial than ROC22 on the activity of rhizosphere microorganism’s soil functionality and sugarcane production.